FUNCIONES GENERALIZADAS DE FRONTERA - Balcázar Huapaya, Claudio Fernando (2012)
In this paper we prove that in general, the restriction of a function space of Sobolev H1(Ω) the boundary of the domain Ω belongs to L2(∂Ω); for the case of boundary regularly provided to be continuous and Lipschitz.